If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 5) + -5(2x + 3) = 22 Reorder the terms: 3(5 + 4x) + -5(2x + 3) = 22 (5 * 3 + 4x * 3) + -5(2x + 3) = 22 (15 + 12x) + -5(2x + 3) = 22 Reorder the terms: 15 + 12x + -5(3 + 2x) = 22 15 + 12x + (3 * -5 + 2x * -5) = 22 15 + 12x + (-15 + -10x) = 22 Reorder the terms: 15 + -15 + 12x + -10x = 22 Combine like terms: 15 + -15 = 0 0 + 12x + -10x = 22 12x + -10x = 22 Combine like terms: 12x + -10x = 2x 2x = 22 Solving 2x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = 11 Simplifying x = 11
| Ln(2x-6)-5=5 | | 5[3y+12]=6[5y+20] | | H=-5t^2+40t+10 | | -128+9p=3p-27 | | -2x-3zx=1-10y | | -128+9p=-3p-27 | | 2x+27x+15= | | 4*-7=41 | | y=15-4i | | 4(Y+22)+1=-5(3-2Y) | | 2(2a+4)-3(a-1)=14 | | 2x+7x+15= | | 5x-(9x+2)=5x-11 | | 2x-8-4x+5=5x+7-3x-10 | | f(x)=x^2-2x+15 | | 9x^2-147x-102= | | 1x+2y(5r)= | | 3x^2-147x-102= | | 8+6p=20 | | 10-p=4 | | 5x-6=12x+62 | | (5x+5)=(3x+5) | | -8x+4=-19x+48 | | 27+53=4x | | (x+8)(x-2)(x+3)(x+2)=0 | | 0.3(2z+7)+2.9=0.5(2z-6) | | 44x^2-30xy+4y^2=0 | | 9x-9=-24x+288 | | -6x+1=10x-47 | | xy-7x=3y | | X+59+70=180 | | 6y-3=19y+62 |